Calcium, phosphate and fluoride ionic release from dental restorative materials for elderly population: an in vitro analysis - Aliberti, Angelo; Garcia-Godoy, Franklin; Borges, Alexandre Luiz Souto; Tribst, João Paulo Mendes; Gasparro, Roberta; Mariniello, Mauro; Ausiello, Pietro (Frontiers in Oral Health, 2025)
IntroductionWith the increasing prevalence of cervical and root lesions in elderly patients, dental filling materials able to release bioactive ions are gaining importance in the restorative treatment. This study evaluated the release of calcium (Ca2+), phosphate (PO43−), and fluoride (F−) ions from different restorative materials (Equia Forte HT Fil, Stela Self Cure and Riva Self Cure) for elderly population through in vitro testing conducted under different pH levels and temperature conditions.MethodsSpecimens (10 mm diameter and 2 mm thickness; n = 3 for each material) were prepared according to manufacturers’ instructions, immersed in buffer solutions at pH 4.8, 6.8, and 8.8; and stored at 37°C and 44°C. Ion release was measured after 1-, 7-, and 28-days using ion chromatography (fluoride and phosphate ions) and mass spectrometry (calcium ions).ResultsIon release from dental restorative materials was significantly influenced by pH, temperature, and exposure duration. All materials tested exhibited consistent pH trends, with an increase in acidic conditions and stabilization in neutral and basic environments. Fluoride release was notably affected by pH and exposure time (p < 0.001), with Equia Forte HT Fil showing the highest fluoride release (34.59 ± 0.63 mg/L) in a basic environment at 37°C. Stela Self Cure had a maximum release of 3.55 ± 0.24 mg/L, and Riva Self Cure reached 7.67 ± 0.49 mg/L after 28 days at 44°C in an acidic medium. Phosphate release remained stable, while calcium ion release varied significantly among materials. Stela Self Cure had the highest calcium release (14.35 ± 0.45 mg/L) in a basic environment, and Equia Forte HT Fil showed the highest calcium concentration (30.60 ± 0.73 mg/L) in neutral conditions.ConclusionsThe study highlights the relevance of ion-releasing from some bioactive dental restorative materials commonly employed also for managing Class V cervical lesions and promote remineralization in aging oral environments. Materials tested showed variable fluoride, calcium, and phosphate release depending on pH, temperature, and time. Equia Forte HT Fil and Riva Self Cure exhibited higher fluoride release, supporting anti-caries potential.